Evaluating the Application of Using Korean Idols as Local Brand Ambassador Skincare Toward Consumer Satisfaction - Sekar Aruni, Raihandifa; Februadi, Agustinus C (Journal of Marketing Innovation (JMI), 2023)
Local skincare still uses the perfect-looking skin of celebrities such as Korean idols as brand ambassadors to promote their products. There are differences between the skin problems of Indonesians and Korean idols, so it may not meet consumers' expectations of the product. This mismatch can build a negative brand image due to consumer dissatisfaction as they may feel the product does not effectively meet their skincare needs. This study aims to determine consumers' perceptions and satisfaction with local skincare products. Qualitative methods, such as in-depth interviews, were used to collect data from 20 participants who were local skincare users, some of whom were K-pop fans. This approach allowed the researchers to dig deeper into the attitudes, opinions, and experiences of these consumers. The results of this study show that the advertising concept that consumers expect to show progress in the use of the product. Instead of focusing on using Korean idols as local brand ambassadors, brands should use more natural models, which can bring inclusion and diversity